TEST OF α-GLUCOSIDAS ENZYME INHIBITION ACTIVITY FROM ISOLATE ETHYL ACETAT FRACTION OF AREUY KIKUNTI LEAVES (Pothos junghuhnii de Vriese) IN VITRO - Delva Syaputri (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2022)
Diabetes mellitus is a metabolic disorder disease whose cases and prevalence have continued to increase over the last few decades. One of the pharmacological therapies for diabetes mellitus is an agent thatinhibits the activity of α-glucosidase which blocks the breakdown of disaccharides which has an impact on delaying glucose absorption, thereby reducing postprandial glucose levels. Several genera of pothos are widelyused as antidiabetic. In this study, the isolate ethyl acetate fraction from areuy leaves (Pothos junghuhnii de Vriese) was used to identify the active compound by LC-MS spectrophotometry and test its inhibitory activityagainst the enzyme -glucosidase and acarbose as a comparison control. The results of the examination identified the active compound, namely digiprolactone with the formula C11H16O3. The highest percentage of inhibition orinhibition in the ethyl acetate fraction isolate number 06 was 12.897% and number 47 was 51.1% at a concentration of 200 ppm, compared to acarbose 99.7% at a concentration of 10 ppm. The IC50 value for theisolated ethyl acetate fraction number 06 is 844.5 ppm, which is classified as very weak and number 47 is 202.6ppm, which is classified as moderate intensity.Keywords: Diabetes Mellitus; Pothos junghuhnii de Vriese; α-glucosidase inhibition